Iridoid glycosides from Gomphandra tonkinensis Gagnep. - Phan Thị Diễm, Trân; Trần Phương, Hà; Vũ Thị Thanh, Tâm; Tôn Thất Hữu, Đạt; Lê Trung, Hiếu; Cường, Lê Cảnh Việt (Hue University Journal of Science: Natural Science, 2025)
Four iridoid glycosides, namely sweroside (1), loganin (2), triplostoside A (3), and gomphandranoside C (4), were isolated from the roots of Gomphandra tonkinensis Gagnep. collected in Thua Thien Hue. The chemical structures of isolated compounds were determined based on 1D-NMR and 2D-NMR spectral data and compared with previously published information. Compound 1 exhibits the ability to inhibit diabetes-related enzymes (α-amylase and α-glucosidase) with IC50 values ​​of 331.1 ± 8.6 µg/mL and 344.2 ± 6.0 µg/mL, respectively. Compound 2 has α-glucosidase inhibitory activity with an IC50 value of 270.9 ± 9.7 µg/mL. Triplostoside A (3) is isolated from the genus Gomphandra for the first time.